(untitled) (Research, Society and Development, 2022)
This study aims to analyze the medical records of patients undergoing outpatient follow-up by nephrology at the Hospital Regional Público do Araguaia (HRPA), located in the city of Redenção-PA, in the year 2019-2021. This is a cross-sectional, retrospective, quantitative study, whose data were collected from the medical records available at the HRPA nephrology outpatient clinic. About 2711 medical records of patients with nephropathy were analyzed retrospectively, extracting the following information: gender, age group, city of residence, year of care, type of nephropathy and diagnosis or not of diabetes mellitus (DM). According to the sociodemographic profile, it was found that 50.3% of the visits were made to females and 49.7% to males. The main pathology found associated with hemodialysis therapy was chronic kidney disease (CKD), corresponding to 68% of cases, followed by glomerulonephritis with 13.5%, acute renal failure with 3%, and urinary tract infection with 0.5%. Of the others assisted, 8% had other unregistered diagnoses and 1% had no diagnosis. Systemic arterial hypertension together with DM are the main pathologies responsible for cases of CKD and its progression to the end stage of renal disease. The information gathered allows a broad view of the profile of the patient in the nephrology service, and highlights the need for prevention campaigns that reach the population with an increased risk factor, in order to prevent injuries and promote health, generating comprehensive care for the patient. health and quality of life for these patients.